2019
DOI: 10.1101/664029
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SINEUP long non-coding RNA acts via PTBP1 and HNRNPK to promote translational initiation assemblies

Abstract: SINEUPs are long non-coding RNAs (lncRNAs) that contain a SINE element, which up-regulate the translation of target mRNA and have been studied in a wide range of applications for biological and therapeutic tools, although the molecular mechanism is unclear. Here, we focused on the kinetic distribution of target mRNAs and SINEUP RNAs by performing co-transfection of expression vectors for these transcripts into human embryonic normal kidney cells (HEK293T/17) to investigate the network of translational regulati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…We previously found that SINEUP-GFP RNAs localized both in the nucleus and in the cytoplasm when pEGFP-C2 and SINEUP-GFP plasmids were cotransfected [17]. We now found that (m)IVT SINEUP-GFP localized in the cytoplasm regardless of EGFP plasmid transfection (Fig.…”
Section: Ivt Sineup Rnas In Cells Need To Be Stabilized Through Nuclesupporting
confidence: 51%
See 2 more Smart Citations
“…We previously found that SINEUP-GFP RNAs localized both in the nucleus and in the cytoplasm when pEGFP-C2 and SINEUP-GFP plasmids were cotransfected [17]. We now found that (m)IVT SINEUP-GFP localized in the cytoplasm regardless of EGFP plasmid transfection (Fig.…”
Section: Ivt Sineup Rnas In Cells Need To Be Stabilized Through Nuclesupporting
confidence: 51%
“…RNA fluorescence in situ hybridization (FISH) was performed as previously described [17]. Briefly, cells were fixed in 4% paraformaldehyde (Wako) and permeabilized in 0.5% Triton X-100 (Sigma-Aldrich) at room temperature for 5 min.…”
Section: Rna Fluorescence In Situ Hybridizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, our analysis by icSHAPE showed high-enrichment-score protected regions in the T domain, further validating the presence of a single-strand region in this domain in living cells, whereas low-enrichment-score regions in the T domain were preferentially double-stranded as a result of the constraints of the RNAfold software ( Supplementary Figure S5 , see ‘Materials and Methods’ section) ( 38 , 53 ). Thus, our NMR results provide new insights into the RNA regions of inverted SINE B2, and the T domain dynamics may be applicable to binding proteins for SINEUP activity in living cells ( 54 , 55 ). They therefore emphasize the importance of experiment-based structural examination.…”
Section: Discussionmentioning
confidence: 88%
“…However, challenges with in vitro NMR structural analysis still remain, because RNAs adapt to different regulatory states by structural change across different cellular compartments ( 51 ). Because AS-Uchl1 RNAs and synthetic SINEUPs are intercellular mobile elements, nucleocytoplasmic shuttling happens after transcription ( 10 , 55 ). Therefore, different inverted SINE B2 structures may play central roles in the different regulatory states and in different cellular compartments.…”
Section: Discussionmentioning
confidence: 99%